THE ANALYSIS OF METACOGNITIVE AWARNESS OF THE STUDENTS’ WRITNG COMPETENCE - Firlanda Dayu Pramesti; Dias Andris Susanto; Rahmawati Sukmaningrum (Language and Education Journal, 2023)
Metacognitive learning strategies are the main factors influencing the writing skills of explanatory texts (Ramadhanti & Yanda, 2021). This study was a quantitative approach. The questionnaire was distributed to students on Saturday, 11 March 2023, with a processing time of about 20 minutes, where the questionnaire, the MAI, has 52 statement items to measure students’ metacognitive awareness in English. The result shows that overall metacognitive awareness has an average of 8.32, with a very good category. While metacognitive knowledge has an average of 8.18, with the declarative knowledge indicator having a score of 6.65; procedural knowledge has a score of, and conditional knowledge has a score of 8. Meanwhile, metacognitive regulation has an average of 8.47, with the planning indicator having a score of 8.92; information management strategy has a score of 6.75; understanding monitoring has a score of 8.57; prediction strategy has a score of 8.5; and evaluation has a score of 9.64.